Avaliação do padrão de emissão de luz de aparelhos fotopolimerizadores e sua influência na conversão de uma resina composta - Patricia Valente Araujo (2004)
The aim of this study was to compare the pattern of light emission of two light-curing units (a conventional Gnatus Optilight Digital/HAL and a LED Gnatus LED) and to evaluate the influence of this factor in the number of non-reacting monomers of a composite resin (Charisma) by differential scanning calorimetry (DSC). The LED was evaluated with two distinct light tips the acrylic tip of the commercial source (LED A) and an optical fiber tip which was adapted to the conventional device (LED F). Both the emission spectra and the power output of each source were then determined. Specimens of composite resin were photocured for 20 and 40s. Each specimen supplied three samples representing each one of the 3mm of its depth. The samples were then immediately subjected to measurement by DSC. The results obtained showed that the LEDs presented smaller irradiance than did the conventional source but the spectrum of emission of these light-curing units is similar to the absorption spectrum of canphoroquinone. The change in the LED tip improved the light conduction and the LED F obtained results similar to those of the conventional source at 20s exposure. The increase in exposure time didnt affect the results for HAL and LED F and improved the polymerization for LED A, which demanded a longer exposure time to achieve the same conversion of the others light-curing units. The effectiveness of polymerization decreased with the increase of depth, independent of the source evaluated.